Comparison Between Linear Programming And Integer Linear Programming: A Review - Sam, Mei Lee; Saptari, Adi; Salleh, Mohd Rizal; Mohamad, Effendi (Inderscience Enterprises Ltd., 2018)
This research discusses comparison of linear programming (LP) and integer linear programming (ILP). Two techniques to solve LP, simplex method and interior-point method were introduced. For ILP, available algorithms can be classified into exact algorithms and heuristic algorithms. Three criteria were used to evaluate the characteristics: time complexity, problem size and computational time. Simplex method is effective to solve small sized problems with less number of iterations while interior-point method was recommended for large sized problems due to its excellent performance and shorter computational time than simplex method. Exact algorithms are suitable for small sized problems and attain optimal solution in reasonable computational time. Meanwhile, heuristics outperform exact algorithms in solving large sized problem where it can obtain near optimal solution in an acceptable computational time. Heuristics are not guaranteed to obtain optimal solutions, compared to exact algorithms.